Linkage Analysis of SKL, KI, KD, IPK, Materials, Learning Processes and Assessment Plans Includes Materials About, SKL, KI, SD, K4, KD and GPA Determination, Division of Learning Materials and Learning Plans - Pitrawana (Indonesian Journal of Pedagogy and Teacher Education, 2023)
This paper aims to analyze the relationship between SKL, KI, KD, GPA, material, learning process and assessment plan including materials about SKL, KI, SD, K4, KD and GPA determination, division of learning materials and lesson plans. The development of writing materials using the literature study method from related reference sources in order to enrich the scientific treasures in analyzing the interrelationship of SKL, KI, KD, GPA, materials, learning processes and assessment plans includes materials about SKL, KI, SD, K4, KD and determination of GPA, division of learning materials and lesson plans. Based on this study, it was found that the importance of applying the linkage analysis of SKL, KI, KD, GPA, materials, learning processes and assessment plans includes materials about SKL, KI, SD, K4, KD and determination of GPA, division of learning materials and lesson plans.